Sequence lithofacies paleogeography evolution of the Middle Permian Maokou Formation in the northwest margin of the Sichuan Basin - Yang, Wenjie; Tan, Xiucheng; Tang, Dahai; Zhang, Zhaokun; Hu, Xin; Li, Minglong; Zeng, Zixuan; Xiao, Di (Frontiers in Earth Science, 2024)
The present tectonic and stratigraphic distribution characteristics in the northwest margin of Sichuan Basin are complex, which restricts the understanding of sequence lithofacies paleogeography of the Middle Permian Maokou Formation. To investigate the process of tectonic-sedimentary evolution in the Middle Permian Epoch, we use basin-margin outcrop and intra-basin well and seismic data to perform isochronal stratigraphic correlation and restore lithofacies palaeogeography of sequences. The results show two structural sequences, i.e. SSQ1 and SSQ2, and 5 third-order sequences, i.e. SQ1-SQ5, in the Middle Permian Maokou Formation. SSQ1 with stable formation thickness shows a slow transgression-fast regression sequence structure. SSQ2 shows a fast transgression-slow regression sequence structure in the area with large thickness and a sustained transgression-fast regression sequence structure in the area with small thickness owing to thickness differentiation caused by tectonic subsidence. Sedimentological analysis shows that the sequences of SQ1-SQ2 mainly comprise carbonate-ramp sediments, the sedimentary facies of which changes from intermediate ramp to outer ramp as the area depressed topographically from south to north. The sequences of SQ3-SQ5 mainly comprise rimmed carbonate platform sediments; platform margin turned up along Shuangyushi-Jian'ge-Yuanba, and the region on the north subsided rapidly to form slope-basin facies. Lithofacies palaeogeography in the Middle Permian Epoch, the northwest margin of the Sichuan Basin was dominated by extensional stresses in northeast and northwest directions. Tectonic activities are the dominant control on the distribution of two structural sequences and the evolution of carbonate platform types in the Maokou Formation, and sea level change is the dominant control on third-order sequence boundaries and sedimentary facies migration. Thus, the Middle Permian tectono-sedimentary evolution model of the northwest margin of Sichuan Basin is established.Research findings may offer new ideas and theoretical support to promising facies exploration in the Maokou Formation, the northwest margin of the Sichuan Basin.